Ethnobotanical Survey of Plants used in Treatment of Haemorroids in North-Central Nigeria - Chukwu, Maureen; Ayodele, Sami; Edoka , Benjamin (University of Thi-Qar Journal of Science, 2023)
An ethnobotanical survey was conducted to identify and document the plants used in the treatment of haemorrhoids in North-Central, Nigeria. A total of three hundred (300) respondents among whom were herb sellers, herbalists, and traditional medicinal practitioners were consulted and interviewed with the help of structured questionnaires to collect data on the plant species from them. Data were represented tables, bar and pie charts and analyzed using descriptive statistics (frequencies and percentages). A total of forty-eight (48) plant species from twenty-seven (27) families were found to be useful in treatment of haemorrhoids in the area under the study. The most prominent among these being members of the family Euphorbiaceae with 4 species, indicating the utmost importance of this family in the cure of haemorrhoids. Followed by families Amaranthaceae, Compositae, Fabaceae and Meliaceae with 3 species each. The plants were identified using botanical, and common names, and the parts of the plant used were also identified. The study revealed that traditional medicinal practices were widely accepted among the people in the study area, probably because they believed in their effectiveness. The plant parts used ranged from root (8.30%), whole plants (8.30%), leaves (43.80%), stem bark (4.24%), bark (10.43%), stem (6.25%) to fruits, young leaves, stem bark leaves, bulb, fruit cub, juice, leaves and juice, shaft of seeds, and bark and leaves at 2.08% each. Further research should be carried out to identify more plant species in the area that can be used to treat haemorrhoids.